2013
DOI: 10.3109/07420528.2013.784770
|View full text |Cite
|
Sign up to set email alerts
|

Evening types are prone to depression

Abstract: Certain preferences for the timing of daily activities (chronotype) may predispose an individual to sleep problems and mood disorders. In this study, we have examined the link between chronotypes and depression. Participants (N ¼ 6071) were recruited from a random sample of the general population aged 25 to 74 yrs living in defined geographical areas, as part of the National FINRISK Study in 2007 in Finland. Chronotype assessment was based on six items from the original Horne-Ö stberg Morningness-Eveningness Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
120
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(137 citation statements)
references
References 32 publications
16
120
1
Order By: Relevance
“…As sleep–wake timing and diurnal preference have been associated with individual differences in sleep quality,49 metabolism,50 and mental health,51 we also assessed this aspect of sleep. PC1 component explained 34% of the variation across all studied measures within this domain (see Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…As sleep–wake timing and diurnal preference have been associated with individual differences in sleep quality,49 metabolism,50 and mental health,51 we also assessed this aspect of sleep. PC1 component explained 34% of the variation across all studied measures within this domain (see Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…There are natural variations in chronotype at all ages with some showing morning preference and some showing evening preference. Extreme chronotypes are associated with multiple psychiatric disorders (47)(48)(49)(50), and it would be interesting in future studies to determine how molecular rhythms correlate with chronotype. Interestingly, a condition called "sundowning" or "sundown syndrome" affects some 20-40% of older people with dementia or Alzheimer's disease where they become confused, delirious, anxious, and agitated in the evening when the sun goes down, causing them to wander, become combative, and have difficulties sleeping (51).…”
Section: Discussionmentioning
confidence: 99%
“…Since this is the first study examining cognitive reactivity and rumination in relation to chronotype and depression, the size of such effects remains to be further determined. Finally, it should be noted that we used the MCTQ as a measure of chronotype assessment, whereas most prior studies examining the association between chronotype and depression (Chan et al, 2014;Chelminski et al, 1999;Kitamura et al, 2010;Merikanto et al, 2013;Muller et al, 2016a) have used the MorningnessEveningness Questionnaire (Horne & Ostberg, 1976). The MCTQ correlates with the MEQ (r = -0.73) (Zavada et al, 2005) and while the MCTQ reflects actual sleep patterns during work days and free days, the MEQ represents a more global preference for sleep patterns as well as for performing mental and physical activities either in early or late hours (Adan et al, 2012).…”
Section: Effect Of IV On M (A) Effect Of M On Dv (B)mentioning
confidence: 99%
“…Studies have shown a consistent association between eveningness and depressive symptoms (Kitamura et al, 2010;Levandovski et al, 2011;Merikanto et al, 2013;Selvi et al, 2010) or depressive disorder (Antypa et al, 2016;Drennan et al, 1991) with some variability in effect sizes, ranging from large to small. The mechanism underlying this association is largely unclear, however.…”
Section: Introductionmentioning
confidence: 99%